MODERASI BERAGAMA MELALUI PENDIDIKAN ISLAM: INTERNALISASI TOLERANSI DAN PERSAUDARAAN DI ANTARA SISWA GENERASI Z - Surayya, Ely; Ekafitrianda, J.M.; Nasir, Nasir; Husarida, Husarida (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This study aims to analyze the internalization of religious moderation through Islamic Religious Education (PAI) among Gen Z students at UIN Jambi by examining Qur’anic values on tolerance and Islamic brotherhood (ukhuwah Islamiyah) in the context of the social media era. The research employed a descriptive qualitative method with a literature review and field observation approach. The results indicate that PAI plays a strategic role in instilling religious moderation by integrating Qur’anic values such as Surah Al-Hujurat verse 10 on Islamic brotherhood and Surah Al-Kafirun verse 6 on tolerance. This internalization is carried out through dialogical learning methods, thematic tafsir studies, and discussion practices based on contemporary social media issues. Gen Z students are able to develop tolerant attitudes, respect differences, and strengthen brotherhood in digital interactions. The study concludes that the internalization of religious moderation through Qur’anic-based PAI is effective in shaping students’ inclusive religious character in the social media era.